Aberrant functional connectivity between the thalamus and visual cortex is related to attentional impairment in schizophrenia. (30th August 2018) - Yamamoto, Maeri; Kushima, Itaru; Suzuki, Ryohei; Branko, Aleksic; Kawano, Naoko; Inada, Toshiya; Iidaka, Tetsuya; Ozaki, Norio
Highlights: Aberrant thalamocortical functional connectivity (FC) is observed in schizophrenia. FC between the thalamus and sensory areas increased in the patients. FC dysfunction may contribute to attention deficits in these patients. Abstract: Resting-state (rs) functional magnetic resonance imaging (fMRI) studies have revealed dysfunctional thalamocortical functional connectivity (FC) in schizophrenia. However, the relationship between thalamocortical FC and cognitive impairment has not been thoroughly investigated. We hypothesized that aberrant thalamocortical FC is related to attention deficits in schizophrenia. Thirty-eight patients with schizophrenia and 38 matched healthy controls underwent rs-fMRI and task fMRI while performing a Flanker task. We observed decreased left thalamic activation in patients with schizophrenia using task fMRI to determine the thalamic seed. A seed-based analysis using this seed was performed in the whole brain to assess differences in thalamocortical FC between the groups. Significantly worse performance was observed in the patient group. The rs-fMRI analysis revealed significantly increased FC between the left thalamus seed and the occipital cortices/postcentral gyri in patients when compared to controls. In the patient group, significant positive correlations were observed between the degree of FC from the left thalamus to the bilateral occipital gyri, which correspond to the visual cortex, and the Flanker effect. No significant correlation was detected in the control group. These results indicate that aberrant FC between the left thalamus and the visual cortex is related to attention deficits in schizophrenia.